Selenium at the Redox Interface of the Genome, Metabolome and Exposome - Fernandes, Jolyn (Free Radic Biol Med, 2018)
Selenium (Se) is a redox-active environmental mineral that is converted to only a small number of metabolites and required for a relatively small number of mammalian enzymes. Despite this, dietary and environmental Se has extensive impact on every layer of omics space. This highlights a need for global network response structures to provide reference for targeted, hypothesis-driven Se research. In this review, we survey the Se research literature from the perspective of the responsive physical and chemical barrier between an organism (functional genome) and its environment (exposome), which we have previously termed the redox interface. Recent advances in metabolomics allow molecular phenotyping of the integrated genome-metabolome-exposome structure. Use of metabolomics with transcriptomics to map functional network responses to supplemental Se in mice revealed complex network responses linked to dyslipidemia and weight gain. Central metabolic hubs in the network structure in liver were not directly linked to transcripts for selenoproteins but were, instead, linked to transcripts for glucose transport and fatty acid β-oxidation. The experimental results confirm the survey of research literature in showing that Se interacts with the functional genome through a complex network response structure. The results imply that systematic application of data-driven integrated omics methods to models with controlled Se exposure could disentangle health benefits and risks from Se exposures and also serve more broadly as an experimental paradigm for exposome research.